1998
DOI: 10.1002/(sici)1099-0992(199803/04)28:2<257::aid-ejsp871>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Rape myths as neutralizing cognitions: evidence for a causal impact of anti-victim attitudes on men's self-reported likelihood of raping

Abstract: Men's rape myth acceptance (RMA; prejudiced beliefs that serve to exonerate the rapist and blame the victim) has been shown to correlate positively with self‐reported rape proclivity (RP). To explore the causal pathway underlying this correlation, two experiments were conducted in which the relative cognitive accessibility of RMA and RP was varied. Male students were asked to report their RP in the context of a scale assessing attraction toward sexual aggression (Experiment 1) or in response to five realistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
242
1
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 191 publications
(266 citation statements)
references
References 17 publications
12
242
1
10
Order By: Relevance
“…However, a series of studies by Bohner and colleagues appears to show the opposite finding. They found the correlation between rape myth acceptance and rape proclivity was stronger when rape myths were presented first (Bohner et al, 1998;Bohner, Siebler, & Schmelcher, 2006). This suggests that the accessibility of rape myths appears to heighten self-reported rape proclivity rather than men seeking to minimize or excuse their proclivity by citing myths or distortions about rape.…”
Section: Running Head: Expertise In Rapementioning
confidence: 99%
“…However, a series of studies by Bohner and colleagues appears to show the opposite finding. They found the correlation between rape myth acceptance and rape proclivity was stronger when rape myths were presented first (Bohner et al, 1998;Bohner, Siebler, & Schmelcher, 2006). This suggests that the accessibility of rape myths appears to heighten self-reported rape proclivity rather than men seeking to minimize or excuse their proclivity by citing myths or distortions about rape.…”
Section: Running Head: Expertise In Rapementioning
confidence: 99%
“…Taken together, these findings extend the current literature by identifying key behavioral and psychological characteristics that can be targeted for future prevention strategies. Although it is important not to assume that those who indicate a high behavioral propensity will engage in this behavior, related literatures have found that those who score high on offending proclivity share the cognitions found in apprehended offenders (Bohner et al, 1998;Malamuth & Check, 1980). Therefore, the factors identified in this current study may be targeted in treatments and interventions aimed at apprehended offenders.…”
Section: Animal Abuse Proclivity 21mentioning
confidence: 77%
“…In a non-offending sample, the process of motor imagery has been shown to activate the same/similar offence-supportive attitudes and beliefs as those reported by offenders who actually engage in the behavior (e.g., Bohner et al, 1998;Malamuth & Check, 1980). So far, proclivity measures have been successfully applied to unapprehended populations to assess for unreported incidences of rape and fire-setting (Bohner et al, 1998;Gannon & Barrowcliffe, 2012). By adopting this measure, we can learn more about the factors related to animal abuse proclivity within a community sample, and thus, make inferences about perpetrators of animal abuse who are undetected.…”
Section: Current Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The myths can be held by both men and women, and may be associated with the denial of rape victims that they have been raped, as well as denial by the offenders that they are rapists. Some studies have shown a correlation between rape myth acceptance and willingness to consider rape (Check and Malamuth, 1983;Bohner et al, 1998Bohner et al, , 2005.…”
Section: Mediamentioning
confidence: 99%